Synaldis concolor Nees 1811 ... - Gadallah, Neveen S.; Ghahari, Hassan; Peris-Felipo, Francisco Javier; Fischer, Maximilian (Zenodo, 2015)
Synaldis concolor (Nees, 1811) Distribution in Iran. East Azarbaijan (Rastegar et al. 2012), Fars (Lashkari Bod et al. 2010, 2011; Fischer et al. 2011; Khajeh et al. 2014), Qazvin (Ghahari et al. 2011b), East of Iran (no locality cited) (Yari et al. 2014). Distribution outside Iran. Entire Europe to Korea and Russian Sakhalin (Fischer et al. 2011). Afghanistan, Bulgaria, France, Greece, Iceland, Italy, Mongolia, Norway, Poland, Serbia, Switzerland and former Yugoslavia (Yu et al. 2012), Austria, Germany, Netherlands (Fischer 1973a, 1993b; Yu et al. 2012), Czech Republic (Lozan et al. 2010; Yu et al. 2012), England, Ireland (Fischer 1973a, 1993b; Broad et al. 2012; Yu et al. 2012), Hungary (Fischer 1973a, 1993b; Papp 2008; Yu et al. 2012), Korea (Shenefelt 1974; Papp 1994; Papp 2007b; Yu et al. 2012), Lithuania (Shenefelt 1974; Papp 1994; Yu et al. 2012), Madeira Islands (van Achterberg and Aguiar 2009 as Dinotrema concolor), Montenegro (Papp 2009b), Russia (Belokobylskij and Tobias 1997; Yu et al. 2012), ... : Published as part of Gadallah, Neveen S., Ghahari, Hassan, Peris-Felipo, Francisco Javier & Fischer, Maximilian, 2015, An annotated catalogue of the Iranian Alysiinae (Hymenoptera: Braconidae), pp. 1-28 in Zootaxa 3974 (1) on pages 7-8, DOI: 10.11646/zootaxa.3974.1.1, http://zenodo.org/record/288961 ...